COVID-19 in children with somatic pathology - M. S. Rajkovic; S. B. Chuelov; S. K. Pylaeva; D. D. Saveleva; А. А. Chernysheva; S. A. Tosoeva; D. D. Namazova; J. N. Ivanova; A. N. Slatetskaya; A. L. Rossina; М. A. Sayfullin; E. E. Petryaykina; et al. (LLC "Diagnostics and Vaccines", 2024)
The coronavirus infection is a pressing issue in modern healthcare, yet the characteristics of the SARS-CoV-2 infection course in children with comorbidities remain insufficiently studied. The aim of this study was to evaluate the clinical form, severity, and duration of SARS-CoV-2 virus shedding in pediatric patients with somatic diseases, depending on the comorbid pathology. Materials and Methods. A comprehensive single-center retrospective study was conducted, analyzing 314 medical records of patients hospitalized in the infectious diseases department of the Russian Children's Clinical Hospital in Moscow over 11 months in 2022. The inclusion criterion was the presence of a laboratory-confirmed COVID-19 diagnosis. Results. Children with comorbidities were found to be predisposed to a more severe course of SARS-CoV-2 infection compared to the pediatric population in general. Children with hematological diseases were at the highest risk of adverse outcomes from COVID-19. Patients with oncological and hematological diseases and primary immunodeficiencies shed the SARS-CoV-2 virus significantly longer than patients with other somatic pathologies. The duration of SARS-CoV-2 RNA detection in patients with severe COVID-19 was significantly longer, which also correlated with the severity of the underlying somatic disease. Conclusion. Children with comorbidities are at risk for a more severe and prolonged course of SARS-CoV-2 infection.